Think like a programmer : an introduction to creative problem solving - Spraul, V. Anton (San Francisco : No Starch Press, 2012)
"The real challenge of programming isn't learning a language's syntax--it's learning to creatively solve problems so you can build something great. In this one-of-a-kind text, author V. Anton Spraul breaks down the ways that programmers solve problems and teaches you what other introductory books often ignore: how to Think Like a Programmer. Each chapter tackles a single programming concept, like classes, pointers, and recursion, and open-ended exercises throughout challenge you to apply your knowledge. You'll also learn how to: Split problems into discrete components to make them easier to solve: Make the most of code reuse with functions, classes, and libraries pick the perfect data structure for a particular job: Master more advanced programming tools like recursion and dynamic memory: Organize your thoughts and develop strategies to tackle particular types of problems. Although the book's examples are written in C++, the creative problem-solving concepts they illustrate go beyond any particular language; in fact, they often reach outside the realm of computer science. As the most skillful programmers know, writing great code is a creative art--and the first step in creating your masterpiece is learning to Think Like a Programmer"--
Includes index.
Keywords: Computer programming; Creative thinking; Problem solving; COMPUTERS / Programming / General; COMPUTERS / Programming Languages / C++.; COMPUTERS / Software Development & Engineering / General; COMPUTERS / Programming / Algorithms